Efektivitas Program Aplikasi JAKI (Jakarta Kini) Dalam Penyediaan Informasi Publik - Ken Ayu Feelyipa; Evi Priyanti; Hanny Purnamasari (LPPM Universitas Abdurrab, 2026)
This study aims to analyze the effectiveness of the Jakarta Kini (JAKI) application program in providing public information in the DKI Jakarta area. JAKI was developed by the Provincial Government of DKI Jakarta through the Jakarta Smart City Management Unit as part of the city’s transformation toward a smart city focused on transparency, efficiency, and accessibility of public services. This research employs a qualitative descriptive approach to gain an in- depth understanding of the program’s effectiveness using four indicators of effectiveness proposed by Budiani (2007): target accuracy, socialization, objectives, and monitoring. The results show that in terms of target accuracy, JAKI has successfully reached tech-savvy productive groups such as students and office workers, but remains less effective among the elderly and those with low digital literacy. In the aspect of socialization, the government has conducted promotions through social media and public events, yet these efforts have not been fully effective due to the lack of practical guides and direct education for the general public.Regarding program objectives, JAKI has facilitated easier digital access to public services, but still faces technical challenges such as system errors and delayed responses to user reports. For the monitoring aspect, although systems such as Citizen Relation Management (CRM) and JakRespons have been implemented, their execution remains inconsistent and lacks transparency in reporting follow-up actions. Overall, this study concludes that the effectiveness of the JAKI application in providing public information has shown positive progress but is not yet optimal, particularly in terms of equal access, service quality, and sustainable monitoring. It is recommended that the government strengthen socialization efforts, improve technological infrastructure, and conduct regular evaluations to ensure that JAKI becomes an inclusive and reliable public service platform for all citizens in DKI Jakarta.